Saw - Wan, James,|d1977-; Whannell, Leigh (Artisan Home Entertainment Distributed by Lions Gate Home Entertainment; distributed in the Philippines by Viva Video, 2005)
Obsessed with teaching his victims the value of life, a deranged, sadistic serial killer is abducting morally wayward people and forcing them to play horrifric games for their own survival. Faced with impossible choices, each victim must struggle to win back his or her life, or else die trying.